Implementation of Character Education Values in Orphanages (Literature Review) - Merentek, Theo Chanra; Saerang, Hetwi Marselina; Lantang, Dani; Sumual, Shelty Deity Meity (Journal of International Conference Proceedings, 2022)
An orphanage is an institution that replaces the role of parents in nurturing, maintaining, caring for, and educating children. This study aims to describe the implementation of character education values, obstacles, and efforts made in orphanages. This study uses a literature review method. The data collection technique used google scholar with the keywords "implementation of character education values" and "character education in orphanages". The number of articles reviewed is 10 articles. The results of the research from these 10 articles show that the implementation of character education values in orphanages comes from 18 Pancasila character values, but only 3 appear to be implemented consistently, namely religious, tolerant and democratic. The obstacles faced are that it takes a long time to foster children's character due to differences in background, caregivers do not prioritize character education, lack of infrastructure and human resources while the efforts made are to give roles to social volunteers to maximize human resources in fostering foster children, establish cooperation with the community, making orphanages like their own family environment.Keywords: Application of Character Education, Application of Values, Character education values, Orphanages, Pancasila values, the role of caregivers